Perencanaan Strategis Sistem Informasi Pada UPT Perpustakaan (Studi Kasus: UPT Perpustakaan STMIK Palangka Raya) - Arliyana, Arliyana; Riyadli, Hafiz (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2016)
The role of information systems and information technology is indispensable in a variety of fields of work and human resources required to have good quality so it could use the technology appropriately. The library is space that contained a lot of catalogs needed for learning and teachingas media seek knowledge and insight for students and lecturer, then the required information system that can hold all the information about then added data quickly and accurately. Therefore, the library shoidbeable to capitaliz on the presence of information technology to improve the quality of its services. It takes a strategic planning of information systems/information technology that isusedas the basis for the construction of an idea information system and in accordance with user needs.Strategic planning of information systems at the Library STMIK Palangka Raya using the methodology Wardand Peppard (Ward, 2002). With the strategic planning of the library can analyze and evaluate theexisting potential of the entire surroundings of the library in order to develop them selves in accordance with the progress of informationand communication technology as well as libraries have a guide in theform of strategies that should be run in the field of informationtechnolog y to improve its performance.It has a good performance of the library will be able to provide acompetitive advantage for the Organization so that it can continue tocompete in today's global era.